Efeitos do método pré-exaustão na atividade elétrica e hipertrofia muscular: uma revisão narrativa - Lima, Vinício dos Anjos (2022)
Introduction: The use of training methods has been widely explored in the scientific field in an attempt to verify the effectiveness of techniques for maximizing neural and morphological adaptations. Among them, the pre-exhaustion method (PE) has been researched in recent years to maximize gains in hypertrophy and muscle activation. The PE method consists of performing a single-joint exercise to muscle failure and then immediately performing a multi-joint exercise to failure as well. However, there is still little evidence about the technique, especially about its possible physiological adaptations. Objective: To verify the scientific evidence on the effect of the PE method on electrical activity and muscle hypertrophy. Methods: The work is a narrative review of studies that analyzed the effects of PE on electrical activity and muscle hypertrophy. Searches were carried out in the following electronic databases: PubMed, SciELO, LILACS, Web of Science and EBSCOhost. Clinical trials published until July 2022, with samples composed of healthy individuals and that used PE as an intervention protocol, were included. Results: After removing duplicates, reading titles, abstracts and full texts, nine articles were considered eligible, comprising a total of 161 healthy participants (131 men and 30 women). As for muscle activation, PE did not demonstrate significant increases in the electromyographic activity of the target muscle when subjected to the method. However, the method was able to increase the activation of synergistic muscles. For muscle hypertrophy, PE may have a potential effect to generate increases in muscle thickness. Conclusion: It is concluded that PE may not be an effective method to increase the electrical activity of the target muscle while for muscle hypertrophy, there is a positive trend for its effects, however, more studies are needed to verify this outcome.